The Search Dashboard: How Reflection and Comparison Impact Search Behavior - Bateman, Scott; Teevan, Jaime; White, Ryen W. (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI '12)., 2012)
Most searchers do not know how to use Web search engines as effectively as possible. This is due, in part, to search engines not providing feedback about how search behavior can be improved. Because feedback is an essential part of learning, we created the Search Dashboard, which provides an interface for reflection on personal search behavior. The Dashboard aggregates and presents an individual’s search history and provides comparisons with that of archetypal expert profiles. Via a five-week study of 90 Search Dashboard users, we find that users are able to change aspects of their behavior to be more in line with that of the presented expert searchers. We also find that reflection can be beneficial, even without comparison, by changing participants’ views about their own search skills, what is possible with search, and what aspects of their behavior may influence search success. Our findings demonstrate a new way for search engines to help users modify their search behavior for positive outcomes.